Anaplasma infections in ticks and reservoir host from Slovakia - Víchová, Bronislava; Majláthová, Viktória; Nováková, Mária; Stanko, Michal; Hviščová, Ivana; Pangrácová, Lucia; Chrudimský, Tomáš; Čurlík, Ján; Petko, Branislav (Infection, genetics and evolution, 2014)
Anaplasma phagocytophilum is a worldwide distributed bacterium with a significant medical and veterinary importance. It grows within the phagosome of infected neutrophils and is responsible for human granulocytic anaplasmosis (HGA), tick-borne fever (TBF) of small ruminants and cattle, canine and equine granulocytic anaplasmosis, but infects also a great variety of wildlife species. Wild ungulates and rodents are considered reservoirs of infection in natural foci. The objective of this study was to determine the spectrum of animal species involved in the circulation of A. phagocytophilum in Slovakia and to analyze the variability of obtained nucleotide sequences, in order to determine whether genotypes from Slovakia cluster according to host-species or geographical location. Several animal species and vector ticks were screened for the presence of members of the family Anaplasmataceae using PCR based methods. Additional data on the molecular evidence of Anaplasma ovis and Candidatus Neoehrlichia mikurensis are presented. These pathogens were detected in tested sheep flocks and rodents with the mean infection rates of 8.16% and 10.75%, respectively. A. phagocytophilum was genotyped by 16S rRNA and groEL gene sequencing. Bacterial DNA was confirmed in questing ixodid ticks, in domesticated canine, wild rodents and several species of wild ungulates. In European isolates, 16S rRNA gene does not seem to be an appropriate locus for the analyses of heterogeneity as it is too conservative. Similarly, 16S rRNA isolates from our study did not reveal any polymorphisms. All isolates were identical in overlapped region and showed identity with sequences from ticks, horses or ruminants previously isolated elsewhere in the world. On the other hand, the groESL heat shock operon is widely used for determination of diversity and the analyses have already revealed considerable degree of heterogeneity. Tested ungulates were infected with A. phagocytophilum to a considerable extent. High proportions of red and roe deer tested positive and the rates of infection reached over 60.0%. GroEL sequences from canine, wild ungulates and ticks from Slovakia clustered within a clade together with isolates from horses, humans, wild ungulates and ticks from Slovakia or elsewhere in the world. Sequences from rodents clustered apart from those obtained from wild ungulates, ticks and humans. These results suggest that European rodents do not harbour A. phagocytophilum strains with strong zoonotic potential such as those from United States.
Keywords: Ixodes ricinus; zdroje nemoci; Arachnid Vectors; psi; Ixodes; Rodents; Dogs; vysoká zvěř; anaplasmóza; Slovakia; Slovenská republika; Anaplasmosis; Rodentia; zvířata; hlodavci; Wild ungulates; Deer; arachnida jako vektory; klíště; Disease Reservoirs; Anaplasma; Animals